Reinforcement Sensitivity, Moral Cognition, Moral Identity, and Moral Judgment among College students - Amiri, Sohrab; Ghasemi Nava, Amir (International Journal of Applied Behavioral Sciences, 2018)
Introduction: Morality and moral behavior are one of the main themes of psychology. The aim of the present study was to investigate the relationship between reinforcement sensitivity و moral identity, moral cognition and utilitarianism in personal and impersonal moral judgments. Method: Statistical population consisted of 303 students (only males) were randomly selected through multi-stage cluster random sampling method. Results: Results showed a strong relationship between Reinforcement Sensitivity dimensions with moral identity, moral cognition and personal and impersonal moral judgment. The series of multiple regression analyses showed that Fight-Flight-Freeze systems (FFFS) were strongly able to predict moral dimensions of cognition, identity and moral judgment. FFFS were strong predictors in all of moral dimensions. Conclusion: The results expand the understanding of the moral dimensions and indicate how domains of reinforcement sensitivity could explain the moral identity, moral cognition and utilitarianism in moral judgments. Declaration of Interest: None.